1 - 2 = 1
Thank you for the opportunity to help you with your question!
1 - 2 = 1
x/x(x-2) - 2/x(x-2) =1 (making common denominator)
1/x =1 (cancelling (x-2) )
I get the LCM as X(X-2). If I apply LCM to right side of equation to each term to cancel out the fraction, I get
x(x-2) (1/x-2) - 2/x(x-2) . x(x-2) = 1
cancelling x(x-2) x-2=1 x=3. Also, could I have made this quadratic equation set to zero and solved for X, in which case x=2 or x=1.
I am a bit confused on the LCM. I get x(x-2) and you appear to get just (x-2), please explain. Also could solving and setting equation to zero also have worked???
u should make the denominator common.
here x(x-2) is the common denominator.
so multiply numerator and denominator of 1/x-2 by x.
and follow as given in answer.
I see my error. Thanks!!!
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?